Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I understand how you get from 1st to 2nd line but i don't get how the two terms are generated in the first line. I looked up Conditional Expectations but i still couldn't make sense of this. Thank you.

conditional expectation

provenance...

part 1 part 2

share|improve this question
1  
What are the definitions of $A_{0}$ and $S(n)$? –  madprob Feb 14 '13 at 0:45
add comment

2 Answers 2

up vote 1 down vote accepted

It seems that the order of the items being equated is not the best for understanding. It might be better to follow as $$ \mathrm{E}\{A_0\mid S(n)=1\}=\frac{\mathrm{P}\{A_0=1,S(n)=1\}}{\mathrm{P}\{S(n)=1\}} $$ by the definition of conditional probability. $$ \frac{\mathrm{P}\{A_0=1,S(n)=1\}}{\mathrm{P}\{S(n)=1\}}=\frac{\mathrm{E}\{A_0\cdot S(n)\}}{\mathrm{E}\{S(n)\}} $$ which follows if $A_0$ and $S(n)$ are independent and take values in $\{0,1\}$. $$ \frac{\mathrm{E}\{A_0\cdot S(n)\}}{\mathrm{E}\{S(n)\}}=\mathrm{E}\{A_0\}+\frac{\mathrm{E}\{A_0\cdot S(n)\}-\mathrm{E}\{A_0\}\cdot\mathrm{E}\{S(n)\}}{\mathrm{E}\{S(n)\}} $$ which is, of course, simply algebra.

If your question was why the items were ordered as they are, I don't know. Perhaps the important equation that will be used later is $$ \mathrm{E}\{A_0\mid S(n)=1\}=\mathrm{E}\{A_0\}+\frac{\mathrm{E}\{A_0\cdot S(n)\}-\mathrm{E}\{A_0\}\cdot\mathrm{E}\{S(n)\}}{\mathrm{E}\{S(n)\}} $$ and so they wanted that to appear together.

share|improve this answer
    
that's what i was asking: why are the items ordered that way. Thank you –  val Feb 15 '13 at 3:06
add comment

If $\mathbb P(Y\in\{0,1\})=1$ and $X$ is integrable, then $\mathbb E(X\mid Y=1)=\mathbb E(XY)/\mathbb P(Y=1)$ and $\mathbb P(Y=1)=\mathbb E(Y)$ hence, for every real number $a$, $$ \mathbb E(X\mid Y=1)=\frac{\mathbb E(X;Y=1)}{\mathbb P(Y=1)}=\frac{\mathbb E(XY)}{\mathbb E(Y)}=a+\frac{\mathbb E(XY)-a\cdot\mathbb E(Y)}{\mathbb E(Y)}. $$ Apply this to $X=A_0$, $Y=S(n)$, and $a=E(A_0)$.

share|improve this answer
    
OK thanks. I still don't get it (sorry): The part i don't understand well enough (and maybe not expressing myself correctly) is how they are able to jump from E(X|Y=1) to a + [E(XY) - aE(Y)]/E(Y). You seem to get there by first going through the second line of their solution - which is what makes sense to me. (but how do you go the other way?) –  val Feb 14 '13 at 18:38
    
I really do not know what you are asking... Anyway, you might start by noticing that the RHS of the identity in my answer does not depend on $a$. –  Did Feb 14 '13 at 20:25
    
That's fine. I got it now (just slow and thick-headed). What i was looking to understand (how they got first line from (4)) came from solving for lambda in (2) using (3). Thanks again. –  val Feb 14 '13 at 20:40
    
If this was your question, I wonder what is the status of your first comment and I am sorry to say that you are spectacularly bad at asking questions. –  Did Feb 14 '13 at 20:48
    
Did - you have some growing to do. –  val Feb 15 '13 at 6:33
show 1 more comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.